Peer Effects in Academic Outcomes: Evidence from a Natural Experiment - Zimmerman, David J. (The Review of Economics and Statistics, 2003)
I use data from Williams College to implement a quasi-experimental empirical strategy aimed at measuring peer effects in academic outcomes. In particular, I use data on individual students' grades, their SAT scores, and the SAT scores of their roommates. I argue that first-year roommates are assigned randomly with respect to academic ability. This allows me to measure differences in grades of high-, medium-, or low-SAT students living with high-, medium-, or low-SAT roommates. With random assignment these estimates would provide compelling estimates of the effect of roommates' academic characteristics on an individual's grades. I also consider the effect of peers at somewhat more aggregated levels. In particular, I consider the effects associated with different academic environments in clusters of rooms that define distinct social units. The results suggest that peer effects are almost always linked more strongly with verbal SAT scores than with math SAT scores. Students in the middle of the SAT distribution may have somewhat worse grades if they share a room with a student who is in the bottom 15% of the verbal SAT distribution. The effects are not large, but are statistically significant in many models.